High-Intensity Resistance Training with Insufficient Recovery Time Between Bouts Induce Atrophy and Alterations in Myosin Heavy Chain Content in Rat Skeletal Muscle - Alves de Souza, Rodrigo Wagner [UNESP]; Aguiar, Andreo Fernando [UNESP]; Carani, Fernanda Regina [UNESP]; Rocha Campos, Gerson Eduardo; Padovani, Carlos Roberto [UNESP]; Silva, Maeli Dal Pai [UNESP] (Wiley-Blackwell, 2011)
The aim of this study was to test whether high-intensity resistance training with insufficient recovery time between bouts, could result in a decrease of muscle fiber cross-sectional area (CSA), alter fiber-type frequencies and myosin heavy chain (MHC) isoform content in rat skeletal muscle. Wistar rats were divided into two groups: trained (Tr) and control (Co). Tr group were subjected to a high-intensity resistance training program (5 days/week) for 12 weeks, involving jump bouts into water, carrying progressive overloads based on percentage body weight. At the end of experiment, animals were sacrificed, superficial white (SW) and deep red (DR) portions of the plantaris muscle were removed and submitted to mATPase histochemical reaction and SDS-PAGE analysis. Throughout the experiment, both groups increased body weight, but Tr was lower than Co. There was a significant reduction in IIA and IID muscle fiber CSA in the DR portion of Tr compared to Co. Muscle fiber-type frequencies showed a reduction in Types I and IIA in the DR portion and IID in the SW portion of Tr compared to Co; there was an increase in Types IIBD frequency in the DR portion. Change in muscle fiber-type frequency was supported by a significant decrease in MHCI and MHCIIa isoforms accompanied by a significant increase in MHCIIb isoform content. MHCIId showed no significant differences between groups. These data show that high-intensity resistance training with insufficient recovery time between bouts promoted muscle atrophy and a transition from slow-to-fast contractile activity in rat plantaris muscle. Anat Rec, 294: 1393-1400, 2011. (C) 2011 Wiley-Liss, Inc.
Keywords: skeletal muscle; resistance training; myosin heavy chain; atrophy; rat